Three-dimensional modeling of a primary health care clinic in Ho, Ghana: its contribution to student engagement, fundraising, and program planning - Lalith Polepeddi; Elizabeth Barden (Taylor & Francis Group, 2010)
Improvements in computer-based technologies can be leveraged to enhance engagement of remote stakeholders with the health needs of a geographically distant community. Three-dimensional (3D) modeling offers a platform to create detailed spatial representations through which stakeholders can experience improvements in shared understanding as well as increased involvement in community health projects occurring anywhere in the world. This case study describes the development of a 3D model of a community health clinic in rural Ghana used to encourage fundraising and sustain global engagement among students at Northwestern University. The resulting ‘virtual clinic’ was achieved quickly and at little cost, suggesting a broader utility of 3D modeling for global health practitioners for increasing donor engagement and resource mapping.